Análisis técnico de la implementación de un sistema SCADA de monitoreo de area extendida(Wams) en el sistema nacional interconectado del Ecuador - Torre Altamirano, Aharon Bhawan de la (2013)
The state of the art regarding planning, operation and post-operative analysis of Power Systems requires the use of new tools to extend the operating philosophy used in Electrical Transmission Substations to a power system geographically distributed, that is usually composed by several substations, load, power generation and interconnections with other areas. This new concept in the management process of power systems is called WAMS (Wide Area Monitoring System) and involves the use of a combination of phasor measurement technology, communications systems and applications that provide dynamic monitoring of the power system with high precision in measurements. These measurements are synchronized with the time signal of a global positioning system (GPS), and the data updating periods are in the order of milliseconds. These features provide operating engineers, operational planning and postoperative analysis, better tools for monitoring and analysis of power systems. This thesis analyzes the theoretical basis applied to WAMS and phasor measurement in power systems, describes the WAMS architecture and its main components, and depicts the installation and configuration of the elements of WAMS. Subsequently, a description and evaluation of the applications (software) of WAMS available at Centro Nacional de Control de Energía - CENACE, is carried out. A technical analysis of the information obtained from the installed WAMS, as well as a presentation of the first results of the implementation of WAMS in the SNI of Ecuador, are also deployed in this document. Finally, based on the analysis performed, major design elements and strategies for implementation of a generalized WAMS in the SNI of Ecuador are identified.